Learning in executive management education - Pardini, Daniel Jardim; Gonçalves, Carlos Alberto; Azevedo, Ana Cláudia (Revista Ciências Administrativas, 2015)
A new challenge in executive education is to develop distinct learning models from the traditional MBAs and other management courses. Revisiting the literature in management education we adopt the social constructivist epistemological approach to discuss and propose a network learning model in the acquisition of knowledge by executives. The results of the research suggest that the network learning method improves the relationship between executives to change and acquire knowledge and, more than other specific management models, the role of the teacher is facilitate the interrelationship between the participants to discuss their experiences and decisions concerning high complex managerial situations. DOI: 10.5020/2318-0722.2014.v20n1p404